ANALISIS SOFT SKILLS PEGAWAI KANTOR BADAN PERENCANAAN DAERAH (BAPPEDA) KOTA PEKANBARU - adi, yusri adi (Sekolah Tinggi Ilmu Ekonomi Riau, 2019)
This study aims to determine how the conditions of soft skills of BAPPEDA employees in Pekanbaru City. The number of respondents in this study were 50 people. The analytical tool is to use descriptive analysis where the results are known that the soft skill conditions of Pekanbaru Bappeda City employees are good enough